Sensitivitas Metode Bioautografi Kontak dan Agar Overlay dalam Penentuan Senyawa Antikapang - ENI KUSUMANINGTYAS; ESTIE ASTUTI; DARMONO DARMONO (Fakultas Farmasi Universitas Pancasila, 2008)
Bioautography method is a laboratory technique to detect substances inhibiting the growth of tested microorganisms. The sensitivity of contact and agar overlay bioautography Was compared to define a recommended method for detecting antifungal compound. In contact bioautography, n-hexane extract of Alpinia galanga was eluted with dichloromethane and toluene on a thin layer chromatography plate (silica gel GF254). The separated compounds were diffused from chromatogram spots to a Thrichophyton menzagrophytes inoculated Sabouraud Dextrose Agar plate. The plate was incubated at 37°C for 3 days. Inhibition zone was observed and the hRf value was defined. Agar overlay bioautography Was performed by covering chromatogram spots With a molten Sabouraud Dextrose Agar medium seeded by Trichophyton mentagrophytes. After solidification, the chromatogram plate was incubated at 37°C overnight and then was stained with Methyl Thiazole Tetrazolium. The inhibition growth bands were visualized and hRfs value were recorded. A contact bioautography produces oneband while agar overlay bioautography produces four bands. Agar overlay bioautography was therefore more sensitive than contact bioautography.